Joanne A.P. Wilson
Joanne A.P. Wilson graduated from the Duke University School Of Medicine in 1973, becoming the second African-American woman to graduate from Duke's medical school. She joined the Duke faculty in 1986 as Associate Professor and Associate Chief of Gastroenterology for Outpatient Services. In 1995, she became the second woman in the Duke Department of Medicine to achieve the rank of Full Professor.